The Correlation Between Habit in Listening English Song and Student’s Pronunciation Ability at Eleventh Grade of Senior High School 2 Jambi - Rafiqi, Muhammad; Suyadi, Suyadi; Dewi, Kartika (Universitas Batanghari Jambi, 2025)
This research was made to figure out if there is a correlation between habit in listening English song and student’s pronunciation ability that applied to eleventh grade students’ in senior high school number 02 Jambi. The sample of this research were 36 students from Grade XI F11. This research used Quantitative method by using questionnaire. The questionnaire comprised 15 questions pertaining to students’ English song listening habits, categorized into four response options. The result of this research showed that habit in listening English song influence student’s pronunciation ability, such as rxy values (0,182). It means that there was no correlation between habit in listening English song and student’s pronunciation ability (very weak).